Should active injecting drug users receive treatment for chronic hepatitis C? Usuários ativos de drogas injetáveis devem receber tratamento para hepatite crônica tipo C? - Vasileios Papadopoulos; Aikaterini Gogou; Theodora Mylopoulou; Konstantinos Mimidis (Arquivos de Gastroenterologia, 2010)
CONTEXT: Accumulating data propose that active injecting drug users might not differ from the general population in terms of sustained virological response when adherent to therapy for chronic hepatitis C. However, current guidelines contain restrictive recommendations for therapy in this group of patients. OBJECTIVE: Therefore, we evaluated a cohort of chronic hepatitis C patients regarding the potent influence of active drug using on initial informed consent, compliance and sustained virological response to treatment. METHOD: For that purpose, 162 consecutive patients (of which 62 active injecting drug users), who had been evaluated during the last 6 years in our center for chronic hepatitis C and proposed to receive treatment with pegylated interferon alpha and ribavirin, were enrolled. Initial informed consent, compliance, and sustained virological response as well as data regarding age, gender, body mass index, genotype, viral load, coinfection with HBV/HDV/HIV, administered interferon alpha (2a or 2b), liver function tests, liver histology, urban residence, ethnicity, and concomitant use of alcohol were collected and analyzed in respect with injecting drug using. RESULTS: Injecting drug using was positively correlated with male gender (P<0.001), young age (P<0.001), native origin (P = 0.043), and concomitant use of alcohol (P<0.001). Comparable initial informed consent (P = 0.836), compliance (P = 0.879), and sustained virological response (P = 0.132) were observed between injecting drug users and non- injecting drug users. The results were confirmed using a multiple regression model. CONCLUSION: Our data further support that active injecting drug users do not constitute a distinct chronic hepatitis C patient group in terms of initial informed consent, compliance, or sustained virological response. Therefore, injecting drug using should not be a major determinant influencing the decision for treatment of chronic hepatitis C in eligible patients. CONTEXTO: Dados acumulados demonstram que usuários ativos de drogas injetáveis podem não diferir da população em geral em termos de resposta virológica sustentada quando aderentes à terapia para a hepatite crônica C. No entanto, as atuais orientações publicadas contêm recomendações restritivas para a terapia nesse grupo de pacientes. OBJETIVO: Com este propósito, avaliou-se uma coorte de pacientes com hepatite crônica C após consentimento informado inicial, no que diz respeito à influência da droga ativa na adesão e na resposta virológica sustentada ao tratamento. MÉTODOS: Para o efeito, foram convidados 162 pacientes (dos quais 62 ativos usuários de drogas injetáveis), que foram avaliados durante os últimos 6 anos em um centro de referência para a hepatite crônica C e se propuseram a receber tratamento com interferon alfa peguilado e ribavirina. O consentimento inicial, a adesão ao tratamento e a resposta virológica sustentada, bem como dados sobre idade, sexo, índice de massa corporal, genótipo, carga viral, com coinfecção HBV/HDV/HIV, tipo de interferon alfa administrado (2a ou 2b), testes de função hepática, histologia hepática, residência urbana, etnia e uso concomitante de álcool foram coletados e analisados em relação com o uso de drogas injetáveis. RESULTADOS: O uso de drogas injetáveis teve correlação positiva com o sexo masculino (P<0,001), idade (P<0,001), de origem nativa (P = 0,043) e uso concomitante de álcool (P<0,001). Foram observados entre usuários de drogas injetáveis e usuários de drogas não-injetáveis dados comparáveis em relação ao consentimento informado inicial (P = 0,836), adesão (P = 0,879) e resposta virológica sustentada (P = 0,132). Os resultados foram confirmados através de um modelo de regressão múltipla. CONCLUSÃO: Os dados confirmam ainda que usuários ativos de drogas injetáveis não constituem um grupo distinto de paciente com hepatite crônica C em termos de consentimento inicial, adesão, ou a resposta virológica sustentada. Assim, o uso de drogas injetáveis não deve ser um dos principais determinantes que influenciam a decisão para o tratamento da hepatite C crônica em pacientes elegíveis.